Challenges and opportunities for Brazilian coffee cultivation arising from EU Regulation 2023/1115 (EUDR) - Abrahão, Vitor; Trentini, Flavia (Przegląd Prawa Rolnego, 2025)
EU Regulation 2023/1115 (EUDR) stipulates that in order to enter the European Union, commodities such as cattle, palm oil, soy, timber, cocoa, rubber and coffee as well as their respective products will have to come from deforestation-free areas. As the world’s largest coffee producer, Brazil is likely to be one of the countries that will be most affected by the EUDR. The article analyses the implications of the regulation for coffee cultivation in Brazil, comparing the controversial issues that have arisen in the sector. It has been found that the main legal aspects related to the EUDR and the Brazilian coffee sector include the concept of the forest, the role of cooperatives in relation to the definition of operators and traders, the differentiated due diligence regime for small and medium-sized enterprises and the risk criteria for coffee production.